2020
DOI: 10.1128/mbio.02336-20
|View full text |Cite
|
Sign up to set email alerts
|

The Native Microbiome is Crucial for Offspring Generation and Fitness of Aurelia aurita

Abstract: All multicellular organisms are associated with microbial communities, ultimately forming a metaorganism. Several studies conducted on well-established model organisms point to immunological, metabolic, and behavioral benefits of the associated microbiota for the host. Consequently, a microbiome can influence the physiology of a host; moreover, microbial community shifts can affect host health and fitness. The present study aimed to evaluate the significance and functional role of the native microbiota for lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 102 publications
(130 reference statements)
7
80
0
Order By: Relevance
“…Future laboratory work should attempt to carefully manipulate associations between different coral genotypes and microbial symbiotic partners (including Symbiodiniaceae and bacteria) to move toward the generation of gnotobiotic (i.e., known-microbiome) corals for use in functional experiments. This has been shown to be feasible in cnidarian model systems such as Hydra, Nematostella, and Aiptasia (Murillo-Rincon et al, 2017;Domin et al, 2018;Medrano et al, 2019;Costa et al, 2021;Dungan et al, 2021), but is only beginning to be explored in reefbuilding corals and other cnidarians (Lin et al, 2019;Cunning and Baker, 2020;Weiland-Bräuer et al, 2020). Experiments that apply a combination of antibiotics treatments followed by targeted probiotic delivery or "microbiome recovery" treatments will yield insights into whether disturbed coral-associated bacteria communities and host stress response phenotypes can be "rescued" by the re-introduction of one or several beneficial microbes (Peixoto et al, 2017(Peixoto et al, , 2021Rosado et al, 2018;Damjanovic et al, 2019;Assis et al, 2020;Santoro et al, 2021).…”
Section: Implications For Coral Conservation and Disease Intervention...mentioning
confidence: 99%
“…Future laboratory work should attempt to carefully manipulate associations between different coral genotypes and microbial symbiotic partners (including Symbiodiniaceae and bacteria) to move toward the generation of gnotobiotic (i.e., known-microbiome) corals for use in functional experiments. This has been shown to be feasible in cnidarian model systems such as Hydra, Nematostella, and Aiptasia (Murillo-Rincon et al, 2017;Domin et al, 2018;Medrano et al, 2019;Costa et al, 2021;Dungan et al, 2021), but is only beginning to be explored in reefbuilding corals and other cnidarians (Lin et al, 2019;Cunning and Baker, 2020;Weiland-Bräuer et al, 2020). Experiments that apply a combination of antibiotics treatments followed by targeted probiotic delivery or "microbiome recovery" treatments will yield insights into whether disturbed coral-associated bacteria communities and host stress response phenotypes can be "rescued" by the re-introduction of one or several beneficial microbes (Peixoto et al, 2017(Peixoto et al, , 2021Rosado et al, 2018;Damjanovic et al, 2019;Assis et al, 2020;Santoro et al, 2021).…”
Section: Implications For Coral Conservation and Disease Intervention...mentioning
confidence: 99%
“…Other, aposymbiotic scyphozoans host largely species-specific bacterial communities that differ across body parts and life stages [66,67]. The bacterial associates are distinct from the environment, potentially selected via antimicrobial peptides, and involved in asexual reproduction, health, and fitness of the host [68,69].…”
Section: The Associated Bacterial Microbiome Shares Characteristics Wmentioning
confidence: 99%
“…Planulae and propagules of some scyphozoans have been successfully induced to enter metamorphosis using bacteria found in the environment of settled polyps; in particular, larvae of Cassiopea andromeda responded to a species of Vibrio alginolyticus ( Neumann, 1979 ; Hofmann et al, 1996 ), and the propagules (pedal stolons) of Aurelia aurita to a species of Micrococcaceae ( Schmahl, 1985 ). The asexual reproduction and strobilation of A. aurita was severely inhibited in the absence of the native microbiota ( Weiland-Bräuer et al, 2020 ). Moreover, Lee et al (2018) identified OTUs within Chrysaora plocamia and A. aurita most closely related to a suite of metabolically and physiologically diverse microorganisms capable of mediating the interrelated pathways of carbon, nitrogen, sulfur, and phosphorus.…”
Section: Introductionmentioning
confidence: 99%